The City in the Developing World - Potter, Robert,B.; Lioyd-Evans, Sally (England : Prentice Hall, 1998)
A comprehensive introduction to urbanization in developing countries, placing an understanding of the developing world city in its wider global context. The text provides coverage of topics of concern, including environmental sustainability and the structure of Third World cities.
Includes bibliographical reference and index
Keywords: Urbanization -- Developing countries; Cities and towns -- Developing countries; Urban policy -- Developing countries